Autologous Fat Grafting as a Novel Approach to Parastomal Soft-tissue Volume Deficiencies - Wu, Robert C. (Wolters Kluwer Health, 2014)
SUMMARY: The aim of this study is to describe a novel approach to revise maladaptive soft-tissue contour around an ileostomy. A patient with permanent ileostomy suffered from significant defects in soft-tissue contour due to scarring and wound contraction. He underwent autologous fat grafting to achieve sealing of his stoma appliance and improve cosmesis. Due to numerous surgeries, the stoma appliance would not seal and required daily appliance changes. The patient received autologous fat grafting to augment the contour around stoma. A complete fitting of stoma was achieved. The patient is satisfied with stoma sealing and is changing his stoma appliance every 5–7 days without skin excoriation. Autologous fat transfer is an effective approach to treat a subset of stoma patients with complex subcutaneous defects.